Disoriented and Immobile: The Experiences of People with Visual Impairments during and after the Christchurch, New Zealand, 2010 and 2011 Earthquakes. (November 2016) - Good, Gretchen A.; Phibbs, Suzanne; Williamson, Kerry
Introduction: On September 4, 2010, at 4.35 a.m., a shallow 7.1 magnitude earthquake struck the South Island of New Zealand, followed by a deadly 6.3 magnitude aftershock on February 22, 2011, centered under the city of Christchurch, which killed 185 people. This research explores the experiences of 12 visually impaired Christchurch residents who lived through more than 12, 000 aftershocks throughout 2010 and 2011. The participants shared suggestions about how to be better prepared for such an emergency. Methods: Qualitative research involved 12 face-to-face semi-structured interviews conducted in 2011 prior to the fatal February earthquake. In February 2012, seven of the original participants were reinterviewed about how more than a year of earthquakes had affected their lives. Results: Participants highlighted the importance of communication and technology, personal and agency support, orientation and mobility, health, rebuilding independence, rehabilitation, coping, and resilience. Discussion: Participants demonstrated creative problem-solving abilities, resilience, and community spirit. Findings also indicate that older visually impaired persons are vulnerable in disasters, and that more work needs to be done to prepare communities, agencies, families, and individuals for potential disasters. Implications for practitioners: Participants provided suggestions for disaster preparedness for people who have impairments and for the agencies that provide services to people with disabilities.